Peranan PBB sebagai Subjek Hukum Internasional dalam Penyelesaian Sengketa Internasional - Ni Made Mirah Krisna Devi (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The purpose of this paper is to provide a general explanation of how the role of the United Nations, which is an international organization, acts as a mediator in international disputes. Understand how the actual position of the United Nations in international organizations. As well as discussing ways to resolve disputes in the international sphere that are being faced by countries. Settlement of international disputes has various ways and depending on the country concerned, it wants to resolve the dispute peacefully or by force or through an international court. Of course, the UN strives for any disputes that occur between countries to be resolved peacefully, in accordance with the goals of the UN listed in the UN charter.